Highly efficient hydrogen sensors based on Pd nanoparticles supported on boron nitride coated ZnO nanowires. Issue 14 (20th March 2019) - Weber, Matthieu; Kim, Jin-Young; Lee, Jae-Hyoung; Kim, Jae-Hun; Iatsunskyi, Igor; Coy, Emerson; Miele, Philippe; Bechelany, Mikhael; Kim, Sang Sub
Abstract : High selectivity and sensitivity were measured using a novel type of sensor device, based on ZnO nanowires (NWs) coated with a thin layer of boron nitride (BN) decorated with palladium nanoparticles (NPs). Abstract : High selectivity and sensitivity were measured using a novel type of sensor device, based on ZnO nanowires (NWs) coated with a thin layer of boron nitride (BN) decorated with palladium nanoparticles (NPs). Vapor–Liquid–Solid (VLS) growth and Atomic Layer Deposition (ALD) routes, two scalable technologies, have been used for the synthesis of the sensing device nanomaterials. X-Ray Photoelectron Spectroscopy (XPS), Electron Energy Loss Spectroscopy (EELS), Energy-dispersive X-ray (EDX) spectroscopy and Transmission Electron Microscopy (TEM) studies revealed the presence of both the 5 nm layer of BN and metallic Pd NPs around the ZnO NWs. The nanomaterials were then integrated within a miniaturized sensor device in order to measure their performance for H2 detection at different concentrations and temperatures, in the presence of various gases such as C6 H6, C7 H8, C2 H5 OH, and CH3 COCH3 . High hydrogen response signals of 12.28 (±0.61) have been measured, even for H2 concentrations as low as 10 ppm, confirming the efficiency of the novel designed Pd/BN/ZnO NW sensor. Due to the beneficial synergistic effect of ZnO, BN and Pd nanomaterials, the new sensing device clearly outperformed other sensors based on ZnO NWs. In addition, the sensor was resistant to humidity, and hydrogen gas could be detected for concentrations as low as 0.5 ppm. The high performance obtained with the novel Pd/BN/ZnO NW based sensor along with its easy gas phase processing opens new perspectives and opportunities for the sensing community and will hopefully promote the hydrogen economy.